On cold atmospheric-pressure plasma jet induced DNA damage in cells. (22nd October 2020) - Gaur, Nishtha; Kurita, Hirofumi; Oh, Jun-Seok; Miyachika, Saki; Ito, Masafumi; Mizuno, Akira; Cowin, Allison J; Allinson, Sarah; Short, Robert D; Szili, Endre J
Abstract: To investigate the potential role of the hydroxyl radical ( OH) in cold atmospheric plasma (CAP) jet treatment, two fluorescence-based methodologies are utilised to measure DNA strand breaks. The first comprises a model system of a double-stranded DNA oligomer, where the respective strand ends are tagged with fluorophore and quencher molecules; and the second, a cell culture system reporting DNA strand breaks using the γ -H2AX assay. During the various CAP jet treatments, optical emission spectroscopy is used to detect the OH in the gas phase and electron spin resonance is used to detect the OH in solution. The CAP jet production of the OH is shown to correlate to CAP jet induced DNA damage both with the DNA model and in biological cells. Results indicate that the CAP jet induces a higher degree of DNA damage when the CAP plume is in contact with the target solution. The potential of a 'plasma screen' based upon a hydrogel film, as a method to remove the DNA-damaging OH species from reaching skin cells, is shown to significantly reduce DNA damage whilst facilitating the delivery of hydrogen peroxide. These findings could aid in the development of CAP jet-based applications where DNA damage is the objective (e.g. in cancer treatment) and others where it is to be avoided, e.g. in open-wound treatment and dermatology.